Desenvolvimento de uma base de dados e de indicadores para projetos de pesquisa em rede com ruminantes - Martins, Jorge Dubal (2016)
This thesis aims to describe the structure and the main features of PampaDB, a computer system associated with a database for network research projects on ruminant production systems. The stored information is structured as follows: a higher level has the data source, which is the basic unit of system work and that gathers metadata about the research project or a survey or an agricultural production unit. The data source is comprised of one or more of the following components: agroecosystem, management system resource, animal, pasture, soil, food and location. Each component can store events or observations. From the data entered in the database, different indicators are calculated and presented in tables and graphs. The query module is free to access and allows you to search based on keywords, time periods and data sources. The PampaDB works on client-server architecture, with the data stored on the server and access being done over the internet.